Negative electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

By dispersing nanosilicon in the lithium aluminate phase and adding an alkali metal aluminate phase with a variety of alkali metal elements, the side reaction problems of the negative electrode active substance during initial charging are solved, and the charge and discharge efficiency and discharge capacity are improved.

CN120226164APending Publication Date: 2025-06-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380079122.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-30
Filing Date
2023-11-15
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

In the prior art, the negative electrode active substance containing Si material is prone to side reactions with Li ions during initial charging, resulting in low alkali resistance and reduced discharge capacity.

Method used

A composite material in which nanosilicon is dispersed in the lithium aluminate phase with high alkali resistance is used as the negative electrode active material, and the pH rise of the negative electrode mixture slurry is suppressed by adding two or more alkali metal aluminate phases of alkali metal elements.

Benefits of technology

The side reactions at the initial charging are effectively reduced, the charge and discharge efficiency is improved, and the discharge capacity is increased by suppressing the oxidation of Si.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120226164A_ABST
    Figure CN120226164A_ABST
Patent Text Reader

Abstract

A negative electrode active material for a non-aqueous electrolyte secondary battery, which is an example of an embodiment, is a composite particle (30) containing an alkali metal aluminate phase (31) containing two or more alkali metal elements and Al, a silicon phase (32) dispersed in the alkali metal aluminate phase (31), and a conductive layer (34) formed on the surface of a mother particle (33), the mother particles are formed from an alkali metal aluminate phase (31) and a silicon phase (32).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a negative electrode active material for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery using the same. Background Art

[0002] In recent years, non-aqueous electrolyte secondary batteries such as lithium ion batteries have been widely used in applications that require high capacity, such as in-vehicle use and power storage use. As a main constituent element of the negative electrode, the negative electrode active material is one of the important factors in achieving a high capacity of the battery, and thus various studies have been conducted on the negative electrode active material. Among them, as a negative electrode active material having a high theoretical capacity density, the use of a silicon-containing material (Si-containing material) has attracted attention.

[0003] As the above Si-containing material, a material in which nano-silicon is dispersed in a SiO2 phase (hereinafter referred to as "SiOx"), Li 2z SiO 2+z a material in which nano-silicon is dispersed in a lithium silicate phase represented by (0 < z < 2) (hereinafter referred to as "LSX") and the like (for LSX, for example, refer to Patent Document 1).

[0004] Prior Art Documents

[0005] Patent Documents

[0006] Patent Document 1: Pamphlet of International Publication No. 2016 / 35290 Summary of the Invention

[0007] Compared with SiOx, LSX has a small irreversible capacity and excellent initial charge-discharge efficiency. However, the lithium aluminate phase in LSX has low alkali resistance, and a side reaction with Li ions still sometimes occurs during the initial charging, and further improvement of the initial charge-discharge efficiency is required.

[0008] The inventors of the present invention have successfully reduced the side reaction at the initial stage of charging and improved the high charge-discharge efficiency by using a material in which nano-silicon is dispersed in a lithium aluminate phase having high alkali resistance as a negative electrode active material. On the other hand, a new problem of a decrease in discharge capacity has occurred. It is considered that the main reason for the decrease in discharge capacity is that when using this material to prepare a negative electrode binder slurry using water as a dispersion medium, Li contained in the lithium aluminate phase is eluted, increasing the pH of the slurry, and as a result, the oxidation of Si proceeds.

[0009] The negative electrode active material for a non-aqueous electrolyte secondary battery of the present disclosure is characterized in that it is a composite particle, and the composite particle includes: a alkali metal aluminate phase containing two or more alkali metal elements and Al, and a silicon phase dispersed in the alkali metal aluminate phase.

[0010] The non-aqueous electrolyte secondary battery of the present disclosure includes a positive electrode, a negative electrode, and a non-aqueous electrolyte, and the negative electrode contains the above-mentioned negative electrode active material.

[0011] According to the negative electrode active material of the present disclosure, it is possible to suppress the rise in the pH of the negative electrode mixture slurry, and a non-aqueous electrolyte secondary battery with a high capacity can be achieved. In addition, a non-aqueous electrolyte secondary battery using the negative electrode active material of the present disclosure has a higher initial charge-discharge efficiency, for example, compared with the case of using LSX. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a cross-sectional view of a non-aqueous electrolyte secondary battery as an example of an embodiment.

[0013] Figure 2 It is a diagram showing a cross-section of particles of a negative electrode active material as an example of an embodiment. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0014] As described above, a composite material in which nano-silicon is dispersed in a lithium aluminate phase has higher alkali resistance and excellent initial charge-discharge efficiency compared with LSX. However, when preparing a negative electrode mixture slurry using water as a dispersion medium, the pH of the slurry rises and the oxidation of Si occurs. The oxidation of Si proceeds due to the reaction of the following formula, and the higher the pH of the slurry, the more the oxidation of Si is promoted. Thus, since Si becomes SiO2 which is not favorable for charge and discharge, the discharge capacity decreases.

[0015] Si + 2OH - →SiO2 + H2 + 2e -

[0016] 2H2O + 2e - →2OH - + H2

[0017] It should be noted that if the amount of Li in the lithium aluminate phase is increased, the porosity inside the particles decreases, but the pH of the negative electrode mixture slurry rises significantly, and the decrease in the discharge capacity becomes more remarkable.

[0018] The inventors of the present invention conducted in-depth research to solve the above problems, and as a result, found that: by using an alkali metal aluminate phase containing two or more kinds of alkali metal elements as a dispersion phase of nano-silicon, it is possible to suppress the rise in the pH of the slurry. As a result of suppressing the rise in the pH of the slurry, the oxidation of Si is suppressed and the discharge capacity is significantly improved. In addition, even if the addition amount of the alkali metal is increased, the rise in pH can be effectively suppressed, and a high capacity can be ensured.

[0019] Hereinafter, with reference to the accompanying drawings, an example of an embodiment of a negative electrode active material for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery using the negative electrode active material will be described in detail. It should be noted that a mode formed by selectively combining constituent elements of a plurality of the following-described embodiments and modification examples is included in the scope of the present disclosure.

[0020] In the embodiments described below, a non-aqueous electrolyte secondary battery 10 is exemplified. The non-aqueous electrolyte secondary battery 10 is a cylindrical battery in which a wound electrode body 14 is housed in a bottomed cylindrical outer can 16, but the outer casing of the battery is not limited to the bottomed cylindrical outer can. As other embodiments of the non-aqueous electrolyte secondary battery of the present disclosure, a square battery having a square outer can, a coin-shaped battery having a coin-shaped outer can, and a pouch-type battery having an outer casing formed of a laminate sheet including a metal layer and a resin layer can be cited. In addition, the electrode body is not limited to a wound type, and may be a laminated electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated with a separator interposed therebetween.

[0021] Figure 1 FIG. schematically shows an axial cross section of a non-aqueous electrolyte secondary battery 10 as an example of an embodiment. As Figure 1 shown, the non-aqueous electrolyte secondary battery 10 includes a wound electrode body 14, a non-aqueous electrolyte, and an outer can 16 that houses the electrode body 14 and the non-aqueous electrolyte. The electrode body 14 has a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a bottomed cylindrical metal container that is open at one axial end side, and the opening of the outer can 16 is blocked by a sealing body 17. Hereinafter, for the sake of convenience of explanation, the sealing body 17 side of the battery is set as the upper side, and the bottom side of the outer can 16 is set as the lower side.

[0022] The non-aqueous electrolyte has ion conductivity (for example, lithium ion conductivity). The non-aqueous electrolyte may be a liquid electrolyte (electrolyte solution) or a solid electrolyte.

[0023] The liquid electrolyte (electrolyte solution) includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. As the non-aqueous solvent, for example, esters, ethers, nitriles, amides, and a mixed solvent of two or more of them can be used. As an example of the non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and a mixed solvent thereof can be cited. The non-aqueous solvent may also contain a halogenated product (for example, fluoroethylene carbonate, etc.) in which at least a part of the hydrogen of these solvents is substituted with a halogen atom such as fluorine. As the electrolyte salt, a lithium salt such as LiPF6 is used.

[0024] As the solid electrolyte, for example, a solid or gel polymer electrolyte, an inorganic solid electrolyte, etc. are used. The polymer electrolyte contains, for example, a lithium salt and a matrix polymer, or contains a non-aqueous solvent, a lithium salt, and a matrix polymer. As the matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent and gels is used. As the polymer material, for example, a fluororesin, an acrylic resin, a polyether resin, etc. are used. As the inorganic solid electrolyte, for example, a material known in a all-solid-state lithium-ion secondary battery, etc. (for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a halide-based solid electrolyte, etc.) is used.

[0025] The positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode body 14 are all strip-shaped long bodies, and are alternately laminated in the radial direction of the electrode body 14 by being wound into a spiral shape. The negative electrode 12 is formed with a size one turn larger than the positive electrode 11 to prevent lithium precipitation. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction (lateral direction). The separator 13 is formed with a size at least one turn larger than the positive electrode 11. For example, 2 sheets are arranged in a manner of sandwiching the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0026] The positive electrode 11 has a positive electrode core and a positive electrode mixture layer disposed on the positive electrode core. The positive electrode core can use a foil of a metal such as aluminum or an aluminum alloy that is stable within the potential range of the positive electrode 11, a thin film having the metal disposed on the surface layer, etc. The positive electrode mixture layer contains a positive electrode active material, a conductive agent, and a binder, and is preferably formed on both surfaces of the positive electrode core except for the exposed portion where the positive electrode lead 20 is welded. The positive electrode 11 can be manufactured, for example, by coating a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, a binder, etc. on the positive electrode core, drying the coating film, and then compressing to form a positive electrode mixture layer on both surfaces of the positive electrode core.

[0027] The positive electrode mixture layer contains a particulate lithium metal composite oxide as the positive electrode active material. The lithium metal composite oxide is a composite oxide containing metal elements such as Co, Mn, Ni, Al, etc. in addition to Li. The metal element constituting the lithium metal composite oxide is, for example, at least 1 selected from Mg, Al, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Y, Zr, Sn, Sb, W, Pb, and Bi. Among them, it is preferably contains at least 1 selected from Co, Ni, and Mn.

[0028] Examples of the conductive agent contained in the positive electrode mixture layer include carbon blacks such as acetylene black and Ketjen black, graphite, carbon nanotubes (CNT), carbon nanofibers, graphene, and other carbon materials. Examples of the binder contained in the positive electrode mixture layer include fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resins, polyolefins, and the like. In addition, these resins can be used in combination with carboxymethyl cellulose (CMC) or its salts, polyethylene oxide (PEO), and the like.

[0029] The negative electrode 12 has a negative electrode core body and a negative electrode mixture layer disposed on the negative electrode core body. As the negative electrode core body, a foil of a metal stable within the potential range of the negative electrode 12, such as copper or a copper alloy, or a thin film having the metal disposed on the surface layer can be used. The negative electrode mixture layer contains a negative electrode active material, a binder, and, if necessary, a conductive agent, and is preferably formed on both sides of the negative electrode core body except for the exposed portion where the negative electrode lead 21 is welded. The negative electrode 12 can be manufactured by applying a negative electrode mixture slurry containing a negative electrode active material and a binder to the surface of the negative electrode core body, drying the coating film, and then compressing it to form a negative electrode mixture layer on both sides of the negative electrode core body.

[0030] Among the binders contained in the negative electrode mixture layer, similar to the case of the positive electrode 11, fluorine resins, PAN, polyimide, acrylic resins, polyolefins, etc. can be used, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode mixture layer preferably contains CMC or its salts, polyacrylic acid (PAA) or its salts, polyvinyl alcohol (PVA), and the like. Among them, it is suitable to use SBR in combination with CMC or its salts, PAA or its salts. The negative electrode mixture layer can also contain a conductive agent such as CNT.

[0031] The separator 13 uses a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, non-woven fabrics, and the like. Suitable materials for the separator 13 are polyolefins such as polyethylene and polypropylene, cellulose, and the like. The separator 13 can have a single-layer structure or a multilayer structure. In addition, a resin layer with high heat resistance such as an aromatic polyamide resin can be formed on the surface of the separator 13.

[0032] A filler layer containing an inorganic filler can also be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, Mg, and phosphate compounds. The filler layer can be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.

[0033] Insulating plates 18 and 19 are disposed above and below the electrode body 14. Figure 1In the example shown, the positive electrode lead 20 extends toward the sealing body 17 side through the through-hole of the insulating plate 18, and the negative electrode lead 21 extends toward the bottom side of the outer can 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, i.e., the lid 27, which is electrically connected to the internal terminal plate 23, becomes the positive electrode terminal. The negative electrode lead 21 is connected to the inner surface of the bottom of the outer can 16 by welding or the like, and the outer can 16 becomes the negative electrode terminal.

[0034] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 for supporting the sealing body 17 is formed in a part of the side surface portion of the outer can 16 so as to protrude inward. The groove portion 22 is preferably formed in a ring shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 by the groove portion 22 and the opening end portion of the outer can 16 that is fastened to the sealing body 17.

[0035] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a lid 27 are laminated in sequence from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disc shape or a ring shape, and the members other than the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and the insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat generation, the lower valve body 24 deforms and breaks in a manner of pushing the upper valve body 26 toward the lid 27 side, so that the current path between the lower valve body 24 and the upper valve body 26 is cut off. When the internal pressure further rises, the upper valve body 26 breaks, and gas is discharged from the opening portion of the lid 27.

[0036] The following will refer to Figure 2 and explain the negative electrode active material.

[0037] Figure 2 FIG. is a schematic diagram showing a cross section of the composite particle 30 as an example of the embodiment. The negative electrode 12 contains at least the composite particle 30 as the negative electrode active material. The negative electrode active material may be substantially composed only of the composite particle 30, but preferably contains the composite particle 30 and a carbon material. When the composite particle 30 and the carbon material are used in combination as the negative electrode active material, it is easy to balance high capacity and excellent cycle characteristics. In the case of using the composite particle 30 and the carbon material in combination, the content rate of the composite particle 30 is preferably 1% by mass or more and 50% by mass or less, more preferably 2% by mass or more and 30% by mass or less, and particularly preferably 3% by mass or more and 20% by mass or less with respect to the total mass of the negative electrode active material.

[0038] As carbon materials, graphite, graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), etc. can be exemplified. Among them, graphite with excellent charge-discharge stability and less irreversible capacity is preferred. The graphite can be any of artificial graphite such as massive artificial graphite (MAG) and mesocarbon microbeads (MCMB), and natural graphite such as flake graphite, massive graphite, and earthy graphite.

[0039] As Figure 2 shown in the figure, the composite particle 30 includes an alkali metal aluminate phase 31 and a silicon phase 32 dispersed in the alkali metal aluminate phase 31. In addition, the composite particle 30 preferably includes a conductive layer 34 formed on the surface of the mother particle 33, and the mother particle 33 is formed by the alkali metal aluminate phase 31 and the silicon phase 32. The mother particle 33 has an island structure in which fine silicon phases 32 are dispersed in the matrix of the alkali metal aluminate phase 31. As will be described later in detail, the alkali metal aluminate phase 31 contains two or more kinds of alkali metal elements and Al. As the dispersion phase of nano-silicon, by using the alkali metal aluminate phase 31 containing two or more kinds of alkali metal elements, the pH rise of the negative electrode mixture paste is suppressed, and the discharge capacity of the battery is greatly improved.

[0040] The alkali metal aluminate phase 31 has excellent alkali resistance compared with the lithium silicate phase in the LSX particles. Therefore, when the composite particle 30 is used as the negative electrode active material, the side reaction with Li ions during the initial charging is suppressed, and the deterioration of the negative electrode active material accompanied by the side reaction and the reduction of the initial capacity accompanied by the deterioration can be suppressed. That is, the reduction of the initial charge-discharge efficiency can be effectively suppressed.

[0041] The composite particle 30 may also substantially not contain lithium silicate and SiO2. The composite particle 30 may contain lithium silicate and SiO2, but it is preferably in a small amount. The total content rate of lithium silicate and SiO2 in the composite particle 30 is, for example, 10% by mass or less.

[0042] With respect to the total mass of the elements other than oxygen constituting the alkali metal aluminate phase 31 and the silicon phase 32 (mother particle 33), the content rate of Al (MAl) is preferably 4.0% by mass or more and 20.0% by mass or less, more preferably 8.0% by mass or more and 15.0% by mass or less. In addition, with respect to the total mass of the elements other than oxygen constituting the mother particle 33, the content rate of the alkali metal element is preferably 0.5% by mass or more and 10.0% by mass or less, more preferably 1.0% by mass or more and 7.0% by mass or less. When the content rate of Al (MAl) and the content rate of the alkali metal element are within the above ranges, it is easy to obtain an alkali metal aluminate phase with excellent stability and ion conductivity. It should be noted that the above stability includes both chemical stability (alkali resistance) and thermal stability.

[0043] From the viewpoints of the stability of the alkali metal aluminate phase 31, reduction in ionic conductivity and porosity, etc., the ratio of the content rate of the alkali metal element to the content rate of Al (MAl) is preferably 0.1 or more and 2.0 or less, more preferably 0.15 or more and 1.0 or less, and particularly preferably 0.2 or more and 0.5 or less. In addition, the ratio (MO / MAl) of the content rate of O (MO) to the content rate of Al (MAl) is, for example, 0.5 or more and 4.0 or less.

[0044] The content rate (MSi) of Si is preferably 50% by mass or more and 95% by mass or less, more preferably 70% by mass or more and 90% by mass or less, relative to the total mass of the elements other than oxygen constituting the mother particle 33. In this case, it is easy to achieve both high capacity and high durability. The content rate (MSi) of Si is the amount of Si mainly constituting the silicon phase 32.

[0045] In the XRD pattern obtained by X-ray diffraction (XRD) measurement of the composite particle 30 (mother particle 33), a peak derived from the alkali metal aluminate phase is observed near 2θ = x°. For example, when the contained alkali metal elements are two selected from Li, Na, and K, x° is at least one selected from the group consisting of 19.4°, 22.3°, 31.9°, 34.3°, and 37.5°. The X-ray for XRD measurement uses Cu Kα ray. It should be noted that in this specification, near x° means within the range of x ± 1°.

[0046] In the alkali metal aluminate phase 31, a fine Al2O3 phase with high crystallinity may also be dispersed. The Al2O3 phase is distributed in the matrix of the alkali metal aluminate phase 31 in an island shape, for example. In this case, it is easy to suppress the expansion and cracking of the alkali metal aluminate phase 31 accompanying the expansion and contraction of the silicon phase 32, and the effect of improving the cycle characteristics is enhanced. When there is an Al2O3 phase, in the X-ray diffraction pattern of the composite particle obtained by X-ray diffraction measurement, a peak derived from the Al2O3 phase can be observed near 2θ = 25.4°. The content rate of the Al2O3 phase in the composite particle 30 is, for example, 10% by mass or less.

[0047] The mother particle 33 of the composite particle 30 has a sea-island structure in which fine silicon phases 32 as island parts are dispersed in the alkali metal aluminate phase 31 as the sea part. The alkali metal aluminate phase 31 has good ionic conductivity, and the alkali metal aluminate phase 31 enables the smooth absorption and release of Li ions based on the silicon phase 32. In addition, the influence of the expansion and contraction of the silicon phase 32 can be mitigated by the alkali metal aluminate phase 31. The alkali metal aluminate phase 31 may be amorphous, and in this case, the influence of the expansion and contraction of the silicon phase 32 can be mitigated more effectively.

[0048] In the composite particles 30, for example, a plurality of primary particles including an alkali metal aluminate phase 31 and a silicon phase 32 aggregate to form secondary particles. The volume-based median particle diameter (D50) of the composite particles 30 (secondary particles) is, for example, 1 μm or more and 25 μm or less, and may be 4 μm or more and 15 μm or less. In this case, it is easy to relieve the stress generated by the volume change of the composite particles 30 accompanying charge and discharge, and good cycle characteristics can be easily obtained. The surface area of the composite particles 30 also becomes an appropriate size, and a decrease in capacity due to a side reaction with the non-aqueous electrolyte can also be suppressed.

[0049] The volume-based median particle diameter (D50) of the composite particles 30 refers to the particle diameter at which the cumulative frequency becomes 50% starting from the smaller particle diameters in the volume-based particle size distribution. The particle size distribution of the composite particles 30 can be measured using a laser diffraction particle size distribution measuring device (for example, MT3000II manufactured by MicrotracBEL Corp.) with water as the dispersion medium. When the surface of the mother particle 33 is covered with the conductive layer 34, the thickness of the conductive layer 34 is substantially thin enough not to affect the particle diameter of the composite particles 30. Therefore, the particle diameter of the composite particles 30 including the conductive layer 34 can also be regarded as the D50 of the composite particles 30.

[0050] The composite particles 30 can be taken out of the battery by the following method. First, disassemble the battery in a fully discharged state and take out the negative electrode. Wash the negative electrode with anhydrous ethyl methyl carbonate or dimethyl carbonate to remove the non-aqueous electrolyte components. Peel the negative electrode mixture layer from the copper foil serving as the negative electrode core, and crush the mixture layer with a mortar to obtain a sample powder. Next, dry the sample powder in a dry atmosphere for 1 hour, immerse it in weakly boiling 6M hydrochloric acid for 10 minutes to remove elements other than those derived from the composite particles. Then, wash the sample powder with ion-exchanged water, filter it, and dry it at 200 °C for 1 hour. Then, in an oxygen atmosphere, heat it to 900 °C to remove the conductive layer 34, whereby only the mother particles 33 can be separated. It should be noted that the fully discharged state means a state where the depth of discharge (DOD) is 90% or more (the state of charge (SOC) is 10% or less).

[0051] [Alkali metal aluminate phase]

[0052] The alkali metal aluminate phase 31 is a phase of a composite oxide containing two or more alkali metal elements and Al. The alkali metal element is an element belonging to Group 1 in the periodic table, and the alkali metal aluminate phase 31 contains at least two elements selected from the group consisting of Li, Na, K, Rb, Cs, and Fr. Among them, Li, Na, and K are preferred. That is, the alkali metal elements contained in the alkali metal aluminate phase 31 are preferably at least two selected from the group consisting of Li, Na, and K. In this case, the amount of metal elements dissolved in the negative electrode mixture paste can be more effectively reduced, and the improvement effect of the discharge capacity is enhanced.

[0053] The alkali metal aluminate phase 31 preferably contains at least one of Li and Na as the alkali metal element. That is, the alkali metal aluminate phase 31 preferably contains one of Li and Na, and contains one or more selected from the other of Li and Na and K. The alkali metal aluminate phase 31 may contain three or more alkali metal elements, but as long as it contains two alkali metal elements, the above effects can be obtained. When the alkali metal aluminate phase 31 contains two alkali metal elements, the alkali metal elements are preferably Li and Na.

[0054] When the alkali metal aluminate phase 31 contains Li and Na as the alkali metal elements, the ratio (MNa / MLi) of the content rate (MNa) of Na to the content rate (MLi) of Li is preferably 0.2 or more and 100 or less with respect to the total mass of the elements other than oxygen constituting the mother particle 33. MNa / MLi is more preferably 0.4 or more and 60 or less, still more preferably 0.85 or more and 55.5 or less, and may be 0.9 or more and 40 or less, or 0.95 or more and 30 or less, or 1.0 or more and 15.0 or less. If MNa / MLi is within this range, the increase in the pH of the negative electrode mixture slurry is more effectively suppressed, and the discharge capacity is greatly improved.

[0055] In addition to the alkali metal element, Al, and O, the alkali metal aluminate phase 31 may further contain other element M. As an example of the element M, at least one selected from the group consisting of Ca, Mg, Zr, Fe, Si, B, P, and La can be cited. Among them, at least one of Si and B is preferred, and B is more preferred. The alkali metal aluminate phase 31 may contain at least one of Si and B in addition to the alkali metal element, Al, and O, or may substantially contain only B. By adding the element M, for example, the stability and ion conductivity of the alkali metal aluminate phase 31 are improved, and the porosity of the composite particle 30 can be reduced.

[0056] The element M may also form a compound. As this compound, depending on the type of the element M, for example, it may be an oxide of the element M or an aluminate of the element M. The content rate of the element M is, for example, 1.0 mass% or more and 10.0 mass% or less with respect to the total amount of the elements other than oxygen constituting the mother particle 33. The alkali metal aluminate phase 31 may further contain trace elements such as chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), and molybdenum (Mo).

[0057] When the alkali metal aluminate phase 31 contains B, the ratio (MAl / MB) of the content rate (MAl) of Al to the content rate (MB) of B is preferably 1.0 or more and 30 or less, more preferably 1.0 or more and 20 or less, and particularly preferably 1.0 or more and 10.0 or less, relative to the total mass of elements other than oxygen constituting the mother particle 33. If MAl / MB is within this range, the effect of reducing the porosity becomes more significant.

[0058] Before the first charge and discharge, the porosity inside the composite particle 30 is preferably 25% or less, more preferably 20% or less. The porosity refers to the proportion of the pores 35 in the cross-section of the composite particle 30, and is obtained from the scanning electron microscope (SEM) image of the particle cross-section. The lower limit value of the porosity is not particularly limited, and as an example, it is 1%. The pores 35 are present, for example, substantially uniformly throughout the mother particle 33. Each pore 35 is small, and like the silicon phase 32, a plurality of pores 35 may also be present in a dispersed manner throughout the alkali metal aluminate phase 31.

[0059] The porosity of the composite particle 30 is calculated as follows: Using image analysis software (for example, imageJ), the SEM image of the particle cross-section is binarized to extract the area of the pores 35, and the total area of the pores 35 is divided by the total area of the particle cross-section to calculate. Details will be described later. The porosity of the composite particle 30 can be controlled by the calcination temperature of the composite particle 30, the compressive force applied to the particle during calcination, the addition of element M (especially B), etc.

[0060] The composite particle 30 has a Vickers hardness of, for example, 300 HV or more. The conductive layer 34 has almost no effect on the Vickers hardness, so the Vickers hardness of the composite particle 30 is substantially the same as that of the mother particle 33. When the composite particle 30 has a high Vickers hardness, it is easy to suppress the volume change of the silicon phase 32 during charge and discharge, and the deterioration of the particle structure can be reduced. As a result, the effect of improving the cycle characteristics becomes more significant. The Vickers hardness of the composite particle 30 can be 350 HV or more, 400 HV or more, or 500 HV or more.

[0061] The Vickers hardness of the composite particle 30 can be measured using a Vickers hardness tester. Specifically, the composite particle 30 is embedded in a thermosetting resin and polished with 400-mesh abrasive paper to expose the cross-section of the composite particle 30. Further, the cross-section is mirror-finished with 2000-mesh abrasive paper and polishing. The Vickers hardness is measured under the conditions of a load of 1 kg and a holding time of 15 seconds. The upper limit value of the Vickers hardness of the composite particle 30 is not particularly limited, and as an example, it is 1500 HV.

[0062] The content ratios of the alkali metal element, Al, and element M in the alkali metal aluminate phase 31 can be measured, for example, by analyzing the cross-section of the negative electrode mixture layer. First, disassemble the battery in a fully discharged state, take out the negative electrode, wash the negative electrode with anhydrous ethyl methyl carbonate or dimethyl carbonate to remove the non-aqueous electrolyte components, and after drying, use a cross-section polisher (CP) to obtain the cross-section of the negative electrode mixture layer. Next, observe the cross-section of the negative electrode mixture layer using SEM.

[0063] The content of each element in the alkali metal aluminate phase 31 is measured by any of the following methods. In addition, the composition of the alkali metal aluminate phase 31 is determined by the content of each element.

[0064] [Energy Dispersive X-ray (EDX)]

[0065] From the cross-sectional image of the backscattered electron image of the negative electrode mixture layer, randomly select 10 composite particles 30 with a maximum diameter of 5 μm or more, and perform elemental mapping analysis based on EDX for each composite particle 30. Use image analysis software to calculate the contained area of the target element. The observation magnification is preferably 2000 to 20000 times. Average the measured values of the contained areas of the specified elements contained in the 10 particles. Calculate the content of the target element from the obtained average value.

[0066] Hereinafter, the measurement conditions for the desired cross-section SEM-EDX analysis are shown.

[0067] Processing device: JEOL, SM-09010 (Cross Section Polisher)

[0068] Processing conditions: acceleration voltage 6 kV

[0069] Current value: 140 μA

[0070] Vacuum degree: 1×10 -3 ~2×10 -3 Pa

[0071] Measurement device: HITACHI, electron microscope SU-70

[0072] Acceleration voltage during analysis: 10 kV

[0073] Field: Free mode

[0074] Probe current mode: Medium

[0075] Probe current range: High

[0076] Anode Ap.: 3

[0077] OBJ Ap.: 2

[0078] Analysis area: 1 μm square

[0079] Analysis software: EDAX Genesis

[0080] CPS: 20500

[0081] Lsec: 50

[0082] Time constant: 3.2

[0083] [Auger electron spectroscopy (AES)]

[0084] From the cross-sectional image of the reflected electron image of the negative electrode mixture layer, 30 composite particles with a maximum diameter of 5 μm or more are randomly selected from 10 particles, and qualitative and quantitative analysis of elements is performed on each composite particle 30 using an AES analysis device (for example, manufactured by JEOL Ltd., JAMP-9510F). The measurement conditions can be set, for example, to an acceleration voltage of 10 kV, a beam current of 10 nA, and an analysis area of 20 μm φ. The content of the specified elements contained in the 10 particles is averaged to calculate the content.

[0085] It should be noted that EDX analysis and AES analysis are performed on a range of 1 μm or more from the peripheral edge of the cross-section of the composite particle 30 toward the inside.

[0086] [Inductively coupled plasma emission spectrometry (ICP)]

[0087] The sample of the composite particle 30 is completely dissolved in a heated acid solution (a mixed acid of hydrofluoric acid, nitric acid, and sulfuric acid), and the carbon in the solution residue is filtered and removed. Then, the spectral intensities of the respective elements are measured for the filtrate obtained by ICP analysis. Next, a standard curve is prepared using a commercially available standard solution of the element, and the content of each element contained in the composite particle 30 is calculated.

[0088] Quantification of each element can also be performed using an electron probe microanalyzer (EPMA), laser ablation ICP mass spectrometry (LA-ICP-MS), X-ray photoelectron spectroscopy (XPS), etc. In addition, the contents of the alkali metal elements, Al, and B contained in the composite particle 30 can be quantitatively analyzed in accordance with JIS R3105 (1995) (Method for analysis of borosilicate glass). The content of Ca can be quantitatively analyzed in accordance with JIS R3101 (1995) (Method for analysis of soda-lime glass).

[0089] The carbon content in the composite particles 30 can be measured using a carbon / sulfur analyzer (for example, EMIA-520 type manufactured by Horiba, Ltd.). Weigh the sample onto a magnetic plate, add a combustion aid, insert it into a combustion furnace heated to 1350 °C (carrier gas: oxygen), and detect the amount of carbon dioxide gas generated during combustion by infrared absorption. The standard curve is prepared, for example, using carbon steel (carbon content 0.49%) manufactured by Bureau of Analysed Samples, Ltd., and the carbon content of the sample is calculated (high-frequency induction heating furnace combustion - infrared absorption method).

[0090] The oxygen content in the composite particles 30 can be measured using an oxygen / nitrogen / hydrogen analyzer (for example, EGMA-830 type manufactured by Horiba, Ltd.). Place the sample in a Ni capsule, put it together with Sn pellets and Ni pellets that serve as a soldering aid into a carbon crucible heated with a power of 5.75 kW, and detect the released carbon monoxide gas. The standard curve is prepared using the standard sample Y2O3, and the oxygen content of the sample is calculated (inert gas fusion - non-dispersive infrared absorption method).

[0091] The amount of Si constituting the Si phase 32 in the composite particles 30 can be quantified using Si-NMR. The following shows the desired measurement conditions for Si-NMR.

[0092] Measuring device: Solid-state nuclear magnetic resonance spectrometer (INOVA-400) manufactured by Varian

[0093] Probe: Varian 7mm CPMAS-2

[0094] MAS: 4.2 kHz

[0095] MAS speed: 4 kHz

[0096] Pulse: DD (45° pulse + signal reading time 1H decoupling)

[0097] Repetition time: 1200 seconds to 3000 seconds

[0098] Observation width: 100 kHz

[0099] Observation center: Around -100 ppm

[0100] Signal reading time: 0.05 seconds

[0101] Number of accumulations: 560

[0102] Sample amount: 207.6 mg

[0103] [Silicon phase]

[0104] The silicon phase 32 is a phase of elemental Si and repeatedly stores and releases Li ions during the charge and discharge of the battery. Capacity is exhibited through the Faraday reaction in which the silicon phase 32 participates. Since the capacity of the silicon phase 32 is large, the degree of expansion and contraction during charge and discharge is also large, but the silicon phase 32 is dispersed within the alkali metal aluminate phase 31. Therefore, the stress generated by the expansion and contraction of the silicon phase 32 is alleviated by the alkali metal aluminate phase 31.

[0105] The silicon phase 32 is composed of, for example, a plurality of microcrystals. The half-value width of the diffraction peak of the Si(111) plane obtained by XRD measurement of the composite particles 30 (mother particles 33) is used to calculate the microcrystal size of the silicon phase 32 according to the Scherrer formula, which is preferably 30 nm or less, more preferably 20 nm or less, and particularly preferably 15 nm or less. In this case, the volume change of the composite particles 30 caused by the expansion and contraction of the silicon phase 32 during charge and discharge can be reduced, and the effect of improving the cycle characteristics becomes more significant.

[0106] The lower limit value of the microcrystal size of the silicon phase 32 is not particularly limited. As an example, it is 1 nm. An example of a suitable microcrystal size of the silicon phase 32 is 1 nm or more and 15 nm or less, and it can be 5 nm or more and 11 nm or less. When the microcrystal size of the silicon phase 32 is 1 nm or more, for example, the surface area of the silicon phase 32 can be suppressed to be small, so that the deterioration of the silicon phase 32 caused by the generation of irreversible capacity is less likely to occur. When the microcrystal size is 15 nm or less, it is easy to uniformize the expansion and contraction of the silicon phase 32, and the stress generated in the composite particles 30 can be effectively alleviated.

[0107] The silicon phase 32 is, for example, granular at least before the first charge. The average particle diameter of the granular silicon phase 32 is preferably 500 nm or less, more preferably 200 nm or less, and particularly preferably 50 nm or less. After the first charge, the average particle diameter of the silicon phase 32 is preferably 400 nm or less, more preferably 100 nm or less. By refining and dispersing the silicon phase 32, the volume change of the composite particles 30 during charge and discharge becomes smaller, and the structural stability of the composite particles 30 is further improved. The average particle diameter of the silicon phase 32 is measured using a cross-sectional image of the composite particles 30 obtained by SEM. Specifically, the average particle diameter of the silicon phase 32 is obtained by averaging the maximum diameters of any 100 silicon phase 32.

[0108] From the perspective of high capacity, the content rate of the silicon phase 32 in the composite particles 30 is preferably 30% by mass or more, more preferably 35% by mass or more, and particularly preferably 55% by mass or more. From the perspective of ensuring good cycle characteristics, the upper limit of the content rate of the silicon phase 32 is preferably 95% by mass or less, more preferably 75% by mass or less, and particularly preferably 70% by mass or less. In this case, the silicon phase 32 exposed on the surface of the composite particles 30 without being covered by the alkali metal aluminate phase 31 is reduced, and thus the side reaction between the non-aqueous electrolyte and the silicon phase 32 is also suppressed.

[0109] [Conductive layer]

[0110] The composite particles 30 preferably have a conductive layer 34 formed on the surface of the mother particles 33 as described above. The mother particles 33 are formed of an alkali metal aluminate phase 31 and a silicon phase 32. The conductive layer 34 covers at least a part of the surface of the mother particles 33, and preferably substantially covers the entire surface of the mother particles 33. The conductive layer 34 is a thin film layer containing a conductive material, which improves the conductivity of the composite particles 30. The thickness of the conductive layer 34 is preferably thin enough not to affect the particle size of the composite particles 30. Considering the ensuring of conductivity and the diffusibility of Li ions, the thickness of the conductive layer 34 is preferably 1 nm or more and 200 nm or less, more preferably 5 nm or more and 100 nm or less. The thickness of the conductive layer 34 can be measured by observing the cross section of the composite particles using SEM or a transmission electron microscope (TEM).

[0111] The conductive material constituting the conductive layer 34 is preferably a conductive carbon material. As the carbon material, amorphous carbon, graphite (natural graphite, artificial graphite, graphitized mesophase carbon, etc.), soft carbon, hard carbon, etc. can be used. Among them, amorphous carbon is preferred in terms of easily forming a thin conductive layer 34 covering the surface of the mother particles 33. Examples of amorphous carbon include carbon black, calcined products of asphalt, coke, activated carbon, etc.

[0112] [Manufacturing method of composite particles]

[0113] The composite particles 30 can be manufactured, for example, by a manufacturing method including the following first to fifth steps.

[0114] First step: A step of obtaining an alkali metal aluminate (hereinafter referred to as "raw material aluminate") as a raw material.

[0115] Second step: A step of compounding the raw material aluminate and the raw material silicon and dispersing the silicon phase 32 in the alkali metal aluminate phase 31 to obtain a composite intermediate.

[0116] Third step: A step of heat-treating the composite intermediate to obtain a sintered body containing the alkali metal aluminate phase 31 and the silicon phase 32 dispersed in the alkali metal aluminate phase 31.

[0117] Step 4: A step of pulverizing the sintered body to obtain composite particles 30.

[0118] Step 5: A step of forming a conductive layer 34 on the surface of mother particles 33, where the mother particles 33 are formed of an alkali metal aluminate phase 31 and a silicon phase 32.

[0119] [Step 1]

[0120] Step 1 includes, for example, the following steps: a step of mixing an aluminum compound, a compound containing an alkali metal element, and, if necessary, a compound containing element M to obtain a mixture; and a step of roasting the mixture to obtain a raw material aluminate. The roasting is carried out, for example, in an oxidizing atmosphere. The roasting temperature is preferably 400°C or higher and 1200°C or lower, more preferably 700°C or higher and 1100°C or lower.

[0121] Examples of the aluminum compound include alumina, aluminum hydroxide, aluminum carbonate, etc. The aluminum compound can be used alone as one kind, or two or more kinds can be used in combination. Examples of the compound containing an alkali metal element include lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, sodium carbonate, sodium oxide, sodium hydroxide, sodium hydride, potassium carbonate, potassium oxide, potassium hydroxide, potassium hydride, etc.

[0122] As the compound containing element M, a boron compound is preferably used, for example. Examples of the boron compound include boron oxide, boric acid, borax, sodium tetraborate, etc. The boron compound can be used alone as one kind, or two or more kinds can be used in combination.

[0123] In Step 1, aluminum compounds that have not reacted with the compound containing an alkali metal element during the production of the raw material aluminate may remain in the raw material aluminate. When the amount of the aluminum compound is larger than that of the compound containing an alkali metal element, aluminum compounds sometimes remain. When the aluminum compound remaining in the raw material aluminate is Al2O3, an Al2O3 phase dispersed in the alkali metal aluminate phase 31 can be formed in the finally obtained composite particles 30.

[0124] [Step 2]

[0125] In Step 2, for example, while applying a shearing force to a mixture of the raw material aluminate and the raw material silicon, the mixture is pulverized to obtain a finely granulated composite intermediate. As an example, a method of mixing the raw material aluminate and the raw material silicon at a specified mass ratio and using a pulverizing device such as a ball mill to finely granulate the mixture can be cited.

[0126] As the starting silicon, coarse silicon particles with an average particle size of about several μm to several tens of μm can be used. The silicon particles are preferably prepared as follows: the crystallite size of the silicon phase 32 calculated from the half-value width of the diffraction peak attributed to the Si(111) plane in the XRD pattern is 15 nm or less. Note that, without using a pulverization device, silicon nanoparticles and nanoparticles of the starting aluminate can be synthesized and mixed.

[0127] [Step 3]

[0128] In Step 3, for example, while applying pressure to the granulated composite intermediate by hot pressing or the like, the composite intermediate is calcined to obtain a sintered body. The pressure applied to the composite intermediate is, for example, 100 MPa or more, and may be 100 MPa or more and 300 MPa or less. There is a tendency that the higher the pressure in Step 3, the smaller the porosity of the composite particles 30. The calcination of the composite intermediate is preferably carried out in an inert atmosphere (for example, an atmosphere such as argon or nitrogen). The calcination conditions in Step 3 also affect the crystallite of the silicon phase 32. Generally, the higher the calcination temperature, the larger the crystallite size.

[0129] An example of the calcination temperature is 450 °C or more and 1000 °C or less. If the calcination temperature is within this range, it is easy to form a structure in which minute silicon phases 32 are dispersed in the alkali metal aluminate phase 31 with low crystallinity. The starting aluminate is stable at this temperature and hardly reacts with silicon. The calcination temperature is preferably 550 °C or more and 950 °C or less, and more preferably 650 °C or more and 900 °C or less. The calcination time is, for example, 1 hour or more and 10 hours or less. In order to reduce the porosity to 25% or less, calcination is preferably carried out at a temperature of 650 °C or more.

[0130] [Step 4]

[0131] Step 4 is a step of pulverizing the mother particles 33 so that they have a desired particle size distribution. The mother particles 33 are pulverized, for example, to a D50 of 1 μm or more and 25 μm or less.

[0132] [Step 5]

[0133] In the manufacturing process of the composite particles 30 of the present embodiment, Step 5 of forming a conductive layer 34 on the surface of the mother particles 33 is included. The conductive material constituting the conductive layer 34 is preferably a conductive carbon material as described above. As a method of covering the surface of the mother particles 33 with a carbon material, examples include: the CVD method using hydrocarbon gases such as acetylene and methane as raw materials; a method of mixing coal tar pitch, petroleum pitch, phenolic resin, etc. with the mother particles 33 and heating them to carbonize; etc. In addition, carbon black can also be made to adhere to the surface of the mother particles 33.

[0134] In the fifth step, for example, a mixture of mother particles 33 and a carbon material is heated at 700 °C or higher and 950 °C or lower in an inert atmosphere (for example, an atmosphere such as argon or nitrogen), whereby composite particles 30 having a conductive layer 34 formed on the surface of the mother particles 33 are obtained.

[0135] Example

[0136] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.

[0137] <Example 1>

[0138] [Preparation of composite particles]

[0139] (First step)

[0140] Al2O3, Na2CO3, Li2CO3 and B2O3 are mixed, and the mixture is calcined in air at 800 °C for 10 hours to obtain a raw material aluminate. In the first step, the mixing ratios of Al2O3, Na2CO3, Li2CO3 and B2O3 are adjusted so that the respective constituent elements of the alkali metal aluminate phase have the element ratios shown in Table 1. In addition, the raw material aluminate is pulverized until D50 becomes 10 μm.

[0141] (Second step)

[0142] Raw material silicon (3N, D50: 10 μm) is mixed with the raw material aluminate obtained in the first step. In the second step, the mixing ratio of the raw material silicon and the raw material aluminate is adjusted so that the respective elements constituting the composite particles have the element ratios shown in Table 1. The mixture is filled into a pot (made of SUS, volume: 500 mL) of a planetary ball mill (manufactured by FRITSCH, P-5), 24 SUS balls (diameter 20 mm) are placed in the pot and the lid is closed, and the mixture is pulverized at 200 rpm for 50 hours in an inert atmosphere.

[0143] (Third step)

[0144] The powdery mixture obtained in the second step is taken out in an inert atmosphere, and sintered at 700 °C for 4 hours while applying a pressure of 200 MPa using a hot press in the inert atmosphere, whereby a sintered body of the mixture is obtained.

[0145] (Fourth step)

[0146] The sintered body obtained in the third step is pulverized and passed through a 40-μm sieve to obtain mother particles in which a silicon phase is dispersed in an alkali metal aluminate phase.

[0147] (Fifth step)

[0148] Mix coal tar pitch (manufactured by JFE Chemical Corporation, MCP250) with the mother particles obtained in the fourth process. Bake this mixture in an inert atmosphere at 800 °C for 5 hours to form a conductive layer containing a conductive carbon material on the surface of the mother particles. The coverage amount of the conductive layer is 5% by mass based on the total mass of the mother particles and the conductive layer. Then, using a sieve, composite particles with a D50 of the conductive layer of 5 μm are obtained.

[0149] In the XRD pattern of the above composite particles obtained by XRD measurement, peaks derived from the alkali metal aluminate phase and the silicon phase were confirmed. The crystallite size of the silicon phase in the composite particles determined by the above method is 10 nm. In addition, by the above method, the content ratios of Na, Li, Al, B, and Si were determined with respect to the total mass of elements other than oxygen constituting the alkali metal aluminate phase and the silicon phase, and the measurement results are shown in Table 1.

[0150] [Fabrication of negative electrode]

[0151] Use the mixture of the above composite particles and graphite at a mass ratio of 5:95 as the negative electrode active material. Add water to a negative electrode binder containing the negative electrode active material, the Na salt of CMC, and SBR at a mass ratio of 97.5:1:1.5 and stir to prepare a negative electrode binder slurry. Then, coat the negative electrode binder slurry on the surface of a negative electrode core made of copper foil. After drying the coating film, perform rolling to fabricate a negative electrode having a negative electrode binder layer with a density of 1.5 g / cm 3 formed on both sides of the copper foil. Note that the pH of the negative electrode binder slurry was measured, and the measurement results are shown in Table 1.

[0152] [Fabrication of positive electrode]

[0153] Add N-methyl-2-pyrrolidone (NMP) to a positive electrode binder containing lithium cobaltate, acetylene black, and PVDF at a mass ratio of 95:2.5:2.5 and stir to prepare a positive electrode binder slurry. Then, coat the positive electrode binder slurry on the surface of a positive electrode core made of aluminum foil. After drying the coating film, perform rolling to fabricate a positive electrode having a positive electrode binder layer with a density of 3.6 g / cm 3 formed on both sides of the aluminum foil.

[0154] [Preparation of non-aqueous electrolyte]

[0155] Dissolve LiPF6 in a solvent obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of 3:7 (25 °C) at a concentration of 1.0 mol / L to prepare a non-aqueous electrolyte.

[0156] [Fabrication of non-aqueous electrolyte secondary battery]

[0157] With a separator interposed therebetween, a positive electrode and a negative electrode with leads wound thereon are wound to fabricate a wound electrode body. The electrode body is inserted into a housing made of an aluminum laminated film, vacuum dried at 105°C for 2 hours, and then a non-aqueous electrolyte is injected. The opening of the housing is sealed to obtain a non-aqueous electrolyte secondary battery.

[0158] <Examples 2 to 4>

[0159] In the above first step, the mixing ratio of Na2CO3 and Li2CO3 was changed such that the content ratios of the respective elements constituting the composite material became the values shown in Table 1. Other than this, composite particles were synthesized in the same manner as in Example 1, and a non-aqueous electrolyte secondary battery was fabricated.

[0160] <Comparative Example 1>

[0161] In the above first step, Na2CO3 was not added. Other than this, composite particles were synthesized in the same manner as in Example 1, and a non-aqueous electrolyte secondary battery was fabricated.

[0162] <Comparative Example 2>

[0163] In the above first step, Li2CO3 was not added. Other than this, composite particles were synthesized in the same manner as in Example 1, and a non-aqueous electrolyte secondary battery was fabricated.

[0164] [Measurement of Discharge Capacity]

[0165] The battery to be evaluated was subjected to constant current charging at a current of 1 It (800 mA) until the voltage reached 4.2 V in a temperature environment of 25°C, and then constant voltage charging was performed at a voltage of 4.2 V until the current reached 1 / 20 It (40 mA). After a pause of 10 minutes, constant current discharge was performed at a current of 1 It (800 mA) until the voltage reached 2.75 V. The discharge capacity at this time was calculated, and the measurement results are shown in Table 1. The results shown in Table 1 are relative values with the discharge capacity of the battery of Comparative Example 1 set to 100.

[0166] [Table 1]

[0167]

[0168] As shown in Table 1, the batteries of the examples all had higher capacities than those of the comparative examples. That is, compared with the case of using a composite material having a lithium aluminate phase containing only Li as an alkali metal (Comparative Example 1) or a sodium aluminate phase containing only Na as an alkali metal (Comparative Example 2) as the dispersed phase, a composite material having an alkali metal aluminate phase containing Na and Li as the dispersed phase of nano-silicon contributed to the high capacity of the battery. In particular, when the ratio of the content of Na to the content of Li (Na / Li) was 1.0 or more and 10.0 or less, the increase in pH could be more effectively suppressed, and the discharge capacity was significantly improved.

[0169] It should be noted that in the composite material of the embodiment, when other alkali metals (for example, K) are added to replace one of Na and Li, the same results as those of the above embodiment can also be obtained.

[0170] The present disclosure will be further described by the following embodiments.

[0171] Configuration 1: A negative electrode active material for a non-aqueous electrolyte secondary battery, which is a composite particle, and the composite particle includes: an alkali metal aluminate phase containing two or more alkali metal elements and Al, and a silicon phase dispersed in the alkali metal aluminate phase.

[0172] Configuration 2: The negative electrode active material for a non-aqueous electrolyte secondary battery according to Configuration 1, wherein the alkali metal element is at least two selected from the group consisting of Li, Na, and K.

[0173] Configuration 3: The negative electrode active material for a non-aqueous electrolyte secondary battery according to Configuration 2, wherein the alkali metal element is Li and Na.

[0174] Configuration 4: The negative electrode active material for a non-aqueous electrolyte secondary battery according to Configuration 3, wherein, with respect to the total mass of elements other than oxygen constituting the alkali metal aluminate phase and the silicon phase, the ratio (MNa / MLi) of the content rate (MNa) of Na to the content rate (MLi) of Li is 0.2 or more and 100 or less.

[0175] Configuration 5: The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein the alkali metal aluminate phase further includes at least one of Si and B.

[0176] Configuration 6: The negative electrode active material for a non-aqueous electrolyte secondary battery according to Configuration 5, wherein the alkali metal aluminate phase contains at least B, and with respect to the total mass of elements other than oxygen constituting the alkali metal aluminate phase and the silicon phase, the ratio (MAl / MB) of the content rate (MAl) of Al to the content rate (MB) of B is 1.0 or more and 30 or less.

[0177] Configuration 7: The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 6, wherein the porosity inside the particles of the composite particle before the first charge and discharge is 25% or less.

[0178] Configuration 8: The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 7, wherein the composite particle includes a conductive layer formed on the surface of the mother particle, and the mother particle is formed by the alkali metal aluminate phase and the silicon phase.

[0179] Constitution 9: A non-aqueous electrolyte secondary battery including a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the negative electrode contains the negative electrode active material according to any one of Constitutions 1 to 8.

[0180] Description of Reference Numerals

[0181] 10 Non-aqueous electrolyte secondary battery, 11 Positive electrode, 12 Negative electrode, 13 Separator, 14 Electrode body, 16 Outer can, 17 Sealing body, 18, 19 Insulating plate, 20 Positive electrode lead, 21 Negative electrode lead, 22 Groove portion, 23 Internal terminal plate, 24 Lower valve body, 25 Insulating member, 26 Upper valve body, 27 Cover, 28 Air cushion, 30 Composite particle, 31 Alkaline metal aluminate phase, 32 Silicon phase, 33 Mother particle, 34 Conductive layer.

Claims

1. A negative electrode active material for a non-aqueous electrolyte secondary battery, which is a composite particle, and the composite particle includes: A alkali metal aluminate phase containing two or more kinds of alkali metal elements and Al, and A silicon phase dispersed in the alkali metal aluminate phase.

2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein, The alkali metal element is at least two selected from the group consisting of Li, Na, and K.

3. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 2, wherein, The alkali metal elements are Li and Na.

4. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 3, wherein, The ratio (MNa / MLi) of the content rate (MNa) of Na to the content rate (MLi) of Li is 0.2 or more and 100 or less with respect to the total mass of the elements other than oxygen constituting the alkali metal aluminate phase and the silicon phase.

5. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein, The alkali metal aluminate phase further includes at least one of Si and B.

6. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 5, wherein, The alkali metal aluminate phase contains at least B, The ratio (MAl / MB) of the content rate (MAl) of Al to the content rate (MB) of B is 1.0 or more and 30 or less with respect to the total mass of the elements other than oxygen constituting the alkali metal aluminate phase and the silicon phase.

7. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein, The porosity inside the particle of the composite particle before the first charge and discharge is 25% or less.

8. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein, The composite particle includes a conductive layer formed on the surface of a mother particle, and the mother particle is formed of the alkali metal aluminate phase and the silicon phase.

9. A non-aqueous electrolyte secondary battery, which includes: a positive electrode, a negative electrode, and a non-aqueous electrolyte, The negative electrode contains the negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Negative electrode active material for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery

    WO2016035290A1